1986
DOI: 10.1007/bf00706808
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial aneurysms and subarachnoid hemorrhage in children and adolescents

Abstract: Thirty-eight cases of symptomatic cerebral aneurysms or spontaneous subarachnoid hemorrhage in children and adolescents were observed from 1965 to 1984; 33 cases were treated from 1970 to date. This group represents 2.6% of the total number of patients with subarachnoid hemorrhage treated at our institute in the same period. The cause of subarachnoid hemorrhage was unknown in 7 cases; an intracranial aneurysm had ruptured in 29 cases, and was unruptured but symptomatic in 2 remaining cases. Three aneurysms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…18,19,26 Aneurysms in children are different from those in adults in several aspects; they are more common in males, with a male to female ratio of almost 3:1, and they tend to be larger, with a higher incidence of giant aneurysms in children compared with adults. [13][14][15]25 Because of the latter difference, aneurysms in children may present with nonhemorrhagic symptoms such as mass effect, headaches, focal neurological deficits, and seizures. The risk of rupture of these aneurysms varied in the literature between 22% and 100% depending on the origin, including dissection, trauma, and infection.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…18,19,26 Aneurysms in children are different from those in adults in several aspects; they are more common in males, with a male to female ratio of almost 3:1, and they tend to be larger, with a higher incidence of giant aneurysms in children compared with adults. [13][14][15]25 Because of the latter difference, aneurysms in children may present with nonhemorrhagic symptoms such as mass effect, headaches, focal neurological deficits, and seizures. The risk of rupture of these aneurysms varied in the literature between 22% and 100% depending on the origin, including dissection, trauma, and infection.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…Approximately 0.5%-4.6% of intracranial aneurysms occur in patients 18 years of age or younger. [1][2][3][4][5][6][7] In a well-known study reported in 1966, only 41 of 6368 ruptured aneurysms were found in patients younger than 19 years. 8 Aneurysms in this population exhibit features that differ significantly from those in adults, including male predominance, a higher incidence of unusual anatomic locations such as the posterior circulation and internal carotid bifurcation, and greater numbers of giant aneurysms.…”
mentioning
confidence: 99%
“…Other reports have commonly observed angiographic vasospasm in children who present with aneurysm rupture but have rarely noted its clinical significance. 10,13,19,21,23,26,38 In children younger than 2 years of age, however, vasospasm can be severe, possibly leading to debilitating large-vessel strokes, 34 probably due to high blood vessel reactivity. Reports on the use of nimodipine to reduce the risk of deficit from clinical vasospasm in children with aneurysmal SAH are limited, although its use in adults has been evaluated in the literature.…”
Section: Treatmentmentioning
confidence: 99%